Analysis and synthesis of speech of hearing impaired - K, Sheela (Journal of All India Institute of Speech and Hearing)
"One of the most recognized but probably least understood concomitants of deafness is a deficit of oral communication skills". (Metz etal., 1982). "Deafness is a fearsome problem largely because of the barrier to communication which it creates. The obvious effect of this barrier is to prevent the deaf from understanding what others say, but it may also impede them from speaking intelligibly. The magnitude of their problem is illustrated by recent studies suggesting that of prelingually deaf children, hearing losses of 90 dB or more, about 75% have speech classified as "barely intelligible" or "worse". (Conrad, 1979).